MD simulation of methane adsorption properties on pillared graphene bubble models - Jiang, Hao; Cheng, Xin-Lu (Journal of molecular modeling, 2019)
Pillared graphene bubble framework is selected as the methane storage vessel in this article. All investigations of methane adsorption are executed by using the MD simulations. The average adsorption energy of methane on different bubble models is between − 4.3 and − 5.2 kcal/mol, which is desirable for absorbing and desorbing gas molecules. The methane adsorption properties of bubble models are obviously different from those of pillared graphene. The effect of graphene interlayer spacing on methane adsorption in selected bubble models can be negligible. Nevertheless, bubble density and temperature have a significant influence on methane adsorption. The amount of adsorbed methane on pillared bubble models at room temperature can reach up to 18.2 mmol/g. This performance of methane adsorption on pillared graphene bubble structures may bring new enlightenment to the investigations of gas storage materials.